Global villain, local savior? What's the role of livestock in sub-Saharan Africa? - Slater, Annabel (2024)
The livestock question is both complex and highly polarized, said Tara Garnett, the director of TABLE—a collaboration between six universities that looks at debates in and around the future of food. She was introducing a panel discussion on 28 March 2024 titled ‘Global villain, local savior? What’s the role of livestock in sub-Saharan Africa?’